Pd(II)-catalyzed C-H Iodination Using Molecular I(2) as the Sole Oxidant - Wang, Xiao-Chen (2013)
Pd-catalyzed ortho-C–H iodination directed by a weakly coordinating amide auxiliary using I(2) as the sole oxidant was developed. This reaction is compatible with a wide range of heterocycles including pyridines, imidazoles, oxazoles, thiazoles, isoxazoles and pyrazoles.